POTENSI ANTIDIABETES EKSTRAK ALOIN PADA MENCIT JANTAN LANSIA OBESITAS DENGAN DIABETES MELITUS TIPE 2 - Fahrezi Maulana; Nadia Purnama Dewi; Ade Teti Vani; Dessy Abdullah (Nusantara Hasana Journal, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia resulting from impaired insulin secretion, insulin resistance, or both. Controlling blood glucose levels is the primary therapeutic goal to prevent complications. The use of medicinal plants as complementary therapy has gained increasing attention, one of which is aloe vera (Aloe vera), which contains aloin and antioxidant compounds with potential antihyperglycemic effects. This study aimed to evaluate the effect of aloin extract administration on blood glucose levels in elderly obese male mice (Mus musculus) with type II diabetes mellitus. This laboratory experimental study employed a pretest–posttest control group design. The subjects were 25-week-old male mice weighing 30–40 grams with random blood glucose levels ≥176 mg/dL. The animals were divided into treatment and control groups. Blood glucose levels were measured before treatment and on days 14 and 28. Data were analyzed using SPSS. The mean baseline blood glucose levels in the treatment and control groups were 182.69 mg/dL and 184.75 mg/dL, respectively. On day 14, the levels decreased to 127.75 mg/dL and 134.88 mg/dL, and on day 28 to 104.62 mg/dL and 121.13 mg/dL. The results demonstrated a significant reduction in blood glucose levels following aloin extract administration. Aloin extract has an effect on lowering blood glucose levels in elderly obese male mice with type II diabetes mellitus.